Cover Feature: Spontaneous Substitutions at Phosphorus Trihalides in Imidazolium Halide Ionic Liquids: Grotthuss Diffusion of Anions? (Chem. Eur. J. 61/2018). Issue 61 (24th October 2018) - Hollóczki, Oldamur; Wolff, Alexander; Pallmann, Julia; Whiteside, Rachel E.; Hartley, Jennifer; Grasser, Matthias A.; Nockemann, Peter; Brunner, Eike; Doert, Thomas; Ruck, Michael
Abstract : Phosphorus halides in 1‐alkyl‐3‐methylimidazolium halide ionic liquids form complex anions. The dynamic exchange of the halides in these complexes—observed by theoretical calculations—suggests the possibility of a structural diffusion of the halide anions in the liquid. Accordingly, potential highly conducting solvents are envisioned, in which substitution reactions at molecular halides in halide ionic liquids can be exploited to increase ion mobilities. More information can be found in the Full Paper by O. Hollóczki, et al. on page 16323 .